Effect of two types of power training in the vertical jump performance in volleyball players - Lombardi, G.; da Silva Vieira, N.; Detanico, D. (Brazilian Journal of Biomotricity, 2011)
The aim of this study was to analyze the effect of two types of strength training (plyometric and weightlifter) in vertical jump performance in volleyball athletes. Sixteen female athletes (13 to 14 years) took part of this study. They underwent a training period of 4 weeks with a frequency of three days per week. We used three distinct groups to sample: plyometric group (PG; n=5), weight training group (WG; n=6) and control group (CG; n=5) that did not participate in specific training for power. The athletes were evaluated for the Counter Movement Jump (CMJ). The t-test for dependent samples and analysis of variance (ANOVA one way) with Tukey test were used with level of significance set at 5%. The results showed significant increase in the vertical jump of WG between pre and post-test (p < 0.05). When analyzing the three groups (PG, WG and CG), no significant differences (p > 0.05) was showed, indicating that the three methods can be used for power training for athletes analyzed.